2022
DOI: 10.3389/fmed.2021.759648
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Variants Within the ABO Blood Group Phenotype Confer Protection Against Critical COVID-19 Hospital Presentation

Abstract: Introduction: Coronavirus disease 2019 (COVID-19) disease severity differs widely due to numerous factors including ABO gene-derived susceptibility or resistance. The objective of this study was to investigate the association of the ABO blood group and genetic variations of the ABO gene with COVID-19 severity in a heterogeneous hospital population sample from the United Arab Emirates, with the use of an epidemiological and candidate gene approach from a genome-wide association study (GWAS).Methods: In this cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…Other SNPs located on the ABO locus were also found to protect the risk of critical illness from COVID-19 infection. These include rs199969472, rs34266669, rs76700116, rs7849280, rs34039247, rs10901251, rs9411475, and rs13291798 ( Jelinek et al, 2022 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other SNPs located on the ABO locus were also found to protect the risk of critical illness from COVID-19 infection. These include rs199969472, rs34266669, rs76700116, rs7849280, rs34039247, rs10901251, rs9411475, and rs13291798 ( Jelinek et al, 2022 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The lower susceptibility associated with blood group O was supported by a recent meta-analysis of 30 studies (Gutiérrez‐Valencia et al, 2022). Additionally, a recent cross-sectional study showed that blood group O offered a protective effect against developing critical COVID-19 ( Jelinek et al, 2022 ). This could arise since human anti-A antibodies, found in patients with blood group O, are hypothesized to bind to the S protein of SARS-CoV-2, thereby hindering its attachment to the ACE2 receptor and preventing its invasion of lung tissue (R. Goel et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, blood type A has been the most associated with severe outcomes, while blood type O frequently appears as a protective factor against the disease progression [ 17 , 18 , 69 , 70 , 77 , [83] , [84] , [85] , [86] , [87] , [88] ]. For instance, although failing to describe a significant difference in ABO phenotype distribution between hospitalized COVID-19 patients and the control group, Muñiz-Diaz et al described a significant positive association between blood type A and mortality, and a significant negative association for blood type O [ 18 ].…”
Section: Associations Between Abo Blood Types and Covid-19mentioning
confidence: 99%
“…In contrast, after finding significantly lower levels of blood type O among critical COVID-19 patients (vs. non-critical patients), Jelinek et al performed a candidate gene approach based on previous GWAS data and examined 240 SNPs in the ABO gene for association with critical COVID-19 presentation. 8 SNPs located at the ABO 3'untranslated region were significantly associated with disease severity, with significantly lower frequencies of the risk alleles in non-critical patients with blood type O [ 83 ].…”
Section: Associations Between Abo Blood Types and Covid-19mentioning
confidence: 99%
See 1 more Smart Citation